Global, regional, and national epidemiology of Intracerebral Hemorrhage among women of childbearing age (1990–2021): incidence, mortality, DALYs, and risk factor analysis - Li, Yuan; Yang, Wei; Xu, Jixiang; Pu, Guoming; Liu, Sujun; Chen, Chunmei; Che, Xiufang; Huang, Hua; Pu, Hongjiang (Frontiers in Neurology, 2025)
Background and ObjectivesIntracerebral Hemorrhage (ICH) is a serious cerebrovascular condition that poses a significant health risk to women of childbearing age (WCBA) globally. However, research specifically focusing on the global impact and trends of ICH among WCBA is limited. This study aims to present data on the burden of ICH among WCBA from 1990 to 2021 across 204 countries and regions, with an emphasis on health disparities, to inform more effective prevention and intervention strategies.MethodsUsing data from the Global Burden of Disease Study (GBD 2021), this study evaluates the global, regional, and national impact of ICH from 1990 to 2021, focusing on incidence, prevalence, mortality, and disability-adjusted life years (DALYs). Temporal trends were analyzed using the estimated annual percentage change (EAPC), and health disparities were assessed using the slope index of inequality. Frontier analysis was employed to identify achievable outcomes based on development levels, and the Bayesian age-period-cohort model was used to project future disease burden trends.ResultsIn 2021, the global burden of ICH among WCBA decreased compared to 1990. There were 231,888 cases (95% UI: 163,211–320,867) and 94,223 deaths (95% UI: 82,659–106,578), with age-standardized incidence and death rates of 11.493 (95% UI: 8.073–15.925) and 4.628 (95% UI: 4.059–5.237) per 100,000 people, respectively. DALYs lost totaled 5,040,596 years (95% UI: 4,432,534–5,654,102), with a DALY rate of 249.334 (95% UI: 222.411–277.622) per 100,000 people. The burden was linked to the Socio-Demographic Index (SDI), with lower SDI regions experiencing increasing burden, while higher SDI regions saw a decline. Regional disparities were observed, and certain factors like environmental particulate pollution showed an upward trend. Projections for 2035 indicate continued decline in both ASDR and ASIR.ConclusionICH in women of reproductive age remains a significant global public health issue. While the overall burden has declined, disparities persist, especially in regions with lower development. Addressing these disparities requires targeted public health interventions, optimized healthcare resource distribution, improved healthcare infrastructure, and health education, in line with the WHO's 2030 health objectives.